2010
DOI: 10.1002/ajpa.21380
|View full text |Cite
|
Sign up to set email alerts
|

Species co‐occurrence patterns and dietary resource competition in primates

Abstract: Diamond (Assembly of species communities. In: Cody ML, Diamond JM, editors. Ecology and evolution of communities. Cambridge: Belknap. p 342-444 (1975)) argued that interspecific competition between species occupying similar niches results in a nonrandom pattern of species distributions. In particular, some species pairs may never be found in the same community due to competitive exclusion. Rigorous analytical methods have been developed to investigate the possible role that interspecific competition has on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 74 publications
0
35
0
Order By: Relevance
“…It was noted, for example, that the biomass of reproductive plant parts, such as flowers and fruits, are much lower than vegetative plant parts, such as leaves (Oates 1987). The repercussions of this are: 1) that leaves can be exploited over a much smaller spatial scale, and 2) that leaves are also less likely to be the targets of feeding competition (Janson and Goldsmith 1995; Kamilar and Ledogar 2011). …”
Section: Socioecological Models and Assumptions Reconsideredmentioning
confidence: 99%
See 1 more Smart Citation
“…It was noted, for example, that the biomass of reproductive plant parts, such as flowers and fruits, are much lower than vegetative plant parts, such as leaves (Oates 1987). The repercussions of this are: 1) that leaves can be exploited over a much smaller spatial scale, and 2) that leaves are also less likely to be the targets of feeding competition (Janson and Goldsmith 1995; Kamilar and Ledogar 2011). …”
Section: Socioecological Models and Assumptions Reconsideredmentioning
confidence: 99%
“…Although it is still sometimes downplayed (Kamilar and Ledogar 2011), feeding competition, including what are loosely termed as scramble and contest competition, occurs regularly in gray langurs and other folivorous primates (see Rank et al 2006 for a discussion of the gray area between these two “types” of competition). Scramble competition generally relates to resources being exploited on a first-come basis; early arrivers to certain patches will benefit by consuming items that are then unavailable to latecomers (van Schaik 1989).…”
Section: Socioecological Models and Assumptions Reconsideredmentioning
confidence: 99%
“…Diamond's (1975) community assembly rule, however, has been contrasted with other explanations for species segregations such as random chance (Connor & Simberloff, 1979;Ulrich, 2004), neutral processes (Bell, 2001(Bell, , 2005 and habitat heterogeneity (Schoener & Adler, 1991). While researchers recognise checkerboards can be used to detect non-random assemblages of species (Gotelli & McCabe, 2002), the interpretation of non-random C-scores remains compromised by the possibility of species segregating due to environmental filtering and dispersal limitations; consequently, uncertainty remains in the interpretation of checkerboards (Boschilia, Oliveira & Thomaz, 2008;Kamilar & Ledogar, 2011). We therefore propose a combined approach to reduce the potential confounding effects of environmental filtering due to habitat heterogeneity and dispersal limitation when analysing observational data.…”
Section: Introductionmentioning
confidence: 99%
“…Sites occupied by invasive tree frogs (Osteopilus septentrionalis) in Florida reduced the probability of occupancy for 2 native species, Hyla cinerea (9 times less likely) and Hyla Squirella (15 times less likely), indicating these species interactions influenced the community assemblage (Waddle et al, 2010). By measuring the proportion of species' pairs that do not co-occur in sets of communities, Kamilar and Ledogar (2011) found that primate communities are not randomly structured and may be the result of interspecific competition. If endangered animals interact with sympatric species, knowledge on the strength and direction of these interactions is important for conservation planning (Acebes et al, 2012;Angelini et al, 2011).…”
Section: Introductionmentioning
confidence: 99%